UZBEKISTAN: NEW VOTING TECHNIQUES IN THE ELECTION CAMPAIGN OF THE 2004 PARLIAMENTARY ELECTION - ISMOILOV, Sukhrobjon (CENTRAL ASIA AND THE CAUCASUS, 2005)
This article is devoted to an analysis of the parliamentary election held on 26 December 2004 in Uzbekistan. The election campaign officially began on 20 September. This time, in contrast to the campaigns of 1994 and 1999 when the people did not have a direct say in the country’s decision-making process, the political parties used new voting techniques and citizens elected candidates to a bicameral representative power body for the first time. This means that from now on Uzbekistan, which is an authoritarian state, will have a parliamentary house formed from representatives of the people and operating on a permanent and professional basis. What is more, the Uzbekistan government made a point of demonstrating that this election was held democratically and that it rendered broad assistance and support to the candidates running for deputy. At a Central Election Commission press conference held on 22 October 2004, it was announced that five of the registered political parties were allowed to run for seats in parliament. 1 And on 1 December, the CEC announced that 74 candidates from the Social-Democratic Party Adolat, 61 from the Democratic Party Milliytiklanish, 119 from the Liberal-Democratic Party, 89 from the National-Democratic Party Fidokorlar, 118 from the People’s Democratic Party, and 56 candidates from independent citizen initiative groups were officially registered to run in the upcoming election. 2 The government allocated a total of 3.3 billion sums (approximately 3.5 million dollars) to support the election campaign. As a result, according to a CEC press release the very next day after the election, 27 December, 12,197,000 (85.1%) of the 14,323,000 citizens registered to vote showed up at the polls. One hundred and twenty voting districts were formed in the country, and approximately 18,000 local observers and a large number of international observers invited by the republic’s government were present at the election.